Increased Susceptibility to Ischemic Brain Injury in Neuroplastin 65-Deficient Mice Likely via Glutamate Excitotoxicity - Hu, Yuhui; Zhan, Qin; Zhang, Haibo; Liu, Xiaoqing; Huang, Liang; Li, Huanhuan; Yuan, Qionglan (Frontiers in Cellular Neuroscience, 2017)
Cell adhesion molecules (CAMs) are involved in synaptic plasticity and neuronal survival in the adult brain. Neuroplastin 65 (Np65), one member of the immunoglobulin superfamily of CAMs, is brain-specific and highly expressed in rodent forebrain. The roles of Np65 in synaptic plasticity have been confirmed, however, whether Np65 affects neuronal survival remains unknown. To address this gap, we generated, to our knowledge, the first Np65 knockout (KO) mice. By occluding middle cerebral artery to perform ischemic stroke model, we showed that Np65 KO mice exhibited more severe neurological deficits and larger infarction volume measured by TTC staining and more apoptotic cells confirmed by TUNEL staining compared to wild type mice. Besides, western blot analysis showed that the vesicular glutamate transporter-1(VGluT1), and N-Methyl D-Aspartate receptors, including NR1, NR2A and NR2B were significantly increased in Np65 KO mice compared with WT mice. In contrast, vesicular gamma amino butyric acid transporter (VGAT) levels were unchanged in two genotypes after stroke. Additionally, phosphorylated-extracellular signal-regulated kinase 1/2 levels were significantly increased in Np65 KO mice compared with WT mice after stroke. Together, these results suggest that Np65 KO mice may be more susceptible to ischemic events in the brain.